Sistem Informasi Reservasi Gedung Aula Berbasis Web di Gedung Aula Balittro - Munggaran, Guruh Putra Bintang; Al Ikhsan, Safaruddin Hidayat; Widhyaestoeti, Dahlia (Universitas Batanghari Jambi, 2025)
The current reservation process for the Balittro Hall is still done manually through WhatsApp messages, leading to message overload and delays in providing fast and accurate service. This study aims to develop a Web-Based Hall Reservation Information System to transition the reservation process from manual to digital, facilitating managers in handling reservation data, and providing more comprehensive and easily accessible information for customers. The research method used is the waterfall model, which involves the stages of analysis, design, implementation, and system testing. The results show that the developed system successfully improves the efficiency of the reservation process and minimizes errors in data management. Customers can also easily access schedule information, hall details, and reservation status online, enhancing their convenience and satisfaction.